THE ROLE OF CLASS I SEMARANG RUPBASAN IN THE MANAGEMENT OF EVIDENCE BASED ON INDONESIAN LAW NUMBER 1 OF 2023 - Aji Haidar, Muhammad Riziq; Wibowo, Apriansyah; Kusuma, Dimas Andrianto; Farhan, Alif; Virasakti A.S, Geraldo; Andika S, Nikola (Fakultas Hukum Universitas Swadaya Gunung Jati, 2025)
Evidence management is a vital part of the criminal justice system which requiring professional and accountable handling. This article explores the role of Semarang Class I RUPBASAN in managing evidence under Law Number 1 of 2023. Using an empirical juridical method, the study combines a normative review of the legal framework with field practices. Primary data were obtained from interviews with RUPBASAN officers and law enforcement officials, while secondary data came from relevant legal documents and literature. The study reveals that Semarang Class I RUPBASAN (Rumah Penyimpanan Benda Sitaan Negara) plays a strategic role in registering, maintaining, and executing evidence, including destruction and auction based on court decisions. However, the implementation of Indonesian Law Number 1 of 2023 faces obstacles such as warehouse overcapacity, risk of evidence damage, and lack of inter-agency coordination. Recommended solutions include modernizing storage facilities, enhancing officer training, and improving collaboration with law enforcement and related agencies. Despite these challenges, the law offers an opportunity to improve transparency and accountability in evidence management.